Molecular azo-imidazole photoswitches: Property tuning by substitution - Jelínková, Veronika; Dellai, Angela; Vachtlová, Martina; Fecková, Michaela; Podlesný, Jan; Klikar, Milan; Castet, Frédéric; Růžička, Aleš; Pařík, Patrik; Pytela, Oldřich; Bureš, Filip (Elsevier Science SA, 2024)
Azo-imidazole photoswitches based on NH- and N-methylimidazole were designed and prepared via a convenient synthetic route. These azo-compounds were investigated by means of XRD analysis, cyclic voltammetry, thermal analysis, UV-Vis absorption spectroscopy and DFT calculations. The photoswitching was mostly affected by imidazole N-substitution with the half-life of (Z)-isomers found within the range of tens of seconds (NHimidazoles) vs. tens of hours (N-methylimidazoles). N-Methylimidazole switches can be further tuned by altering electronic effects of the appended substituents (acyl, bromine, trifluoromethyl and pentafluorosulfanyl). The latter group proved to be particularly interesting in stabilizing (Z)-isomer. Its large half-life (similar to 24 h), high photoconversion (89 %) and diminished nonlinear optical response in contrast to the (E)-isomer (beta(E/Z) - 3.82) point to a very useful strategy in introducing SF5 group in the structure of molecular switches. In summary, this detailed study demonstrates that photoswitching properties of azo-imidazoles can be significantly tuned in a broad extent by (preventing) imidazole tautomerism as well as by altering electronic effects of appended substituents.
Molekulární azo-imidazolové fotopřepínače: modulace vlastností prostřednictvím substituce
Keywords: Imidazole; Photoswitch; Azo-compounds; Second-harmonic generation; E/Z isomerization; Imidazol; fotopřepínač; azosloučenina; E/Z izomerizace